A GRADED RESPONSE MODEL APPROACH TO ASSESS MATHEMATICAL CRITICAL THINKING ON FRACTION PROBLEMS IN JUNIOR HIGH SCHOOL - Pebi Pitri Anasari; Nur Izzati; Metta Liana (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2026)
Abstract Mathematical critical thinking ability (MCTA) plays a crucial role in problem solving and reasoned decision-making, yet many students still struggle with fraction problems, particularly in providing justification, evaluating strategies, and drawing conclusions. This study aims to examine junior high school students' mathematical critical thinking ability in solving fraction problems using a mixed-methods approach. Unlike previous studies, this research integrates qualitative analysis with the Graded Response Model (GRM) to provide a more comprehensive profile of students' critical thinking ability. The participants were 27 seventh-grade students. Data were collected through a mathematical critical thinking test, questionnaires, and semi-structured interviews, and analyzed using the GRM and thematic analysis with methodological triangulation. The findings indicate that most students demonstrated moderate to high levels of mathematical critical thinking. Students with higher ability demonstrated stronger reasoning, justification, and reflection, whereas students across all ability levels struggled to evaluate solution strategies and draw conclusions. These findings highlight the importance of instructional practices that foster mathematical reasoning, evaluation, and justification. Abstrak Kemampuan berpikir kritis matematis (MCTA) berperan penting dalam pemecahan masalah dan pengambilan keputusan, tetapi siswa masih mengalami kesulitan pada materi pecahan, terutama dalam memberikan justifikasi, mengevaluasi strategi, dan menarik kesimpulan. Penelitian ini bertujuan mengkaji kemampuan berpikir kritis matematis siswa SMP dalam menyelesaikan masalah pecahan menggunakan pendekatan mixed methods. Berbeda dari penelitian sebelumnya, studi ini mengintegrasikan analisis kualitatif dengan Graded Response Model (GRM) untuk menghasilkan profil kemampuan yang lebih komprehensif. Partisipan terdiri atas 27 siswa kelas VII. Data diperoleh melalui tes, angket, dan wawancara semi-terstruktur, kemudian dianalisis menggunakan GRM dan analisis tematik dengan triangulasi metode. Hasil menunjukkan sebagian besar siswa berada pada kategori kemampuan tinggi dan sedang. Siswa berkemampuan tinggi menunjukkan penalaran, justifikasi, dan refleksi yang lebih baik, sedangkan seluruh siswa masih lemah dalam mengevaluasi strategi dan menarik kesimpulan. Temuan ini menegaskan pentingnya pembelajaran yang mendorong penalaran, evaluasi, dan justifikasi matematis.